Antihypertensive and Vasorelaxant effects of the ethanolic extract from the stem bark of Aspidosperma tomentosum Mart - Fabíola Fialho Furtado, Camilla Pinheiro de Menezes, Vanderson Barbosa Bernardo, Antônio Euzébio Goulart Santana, Marcos José Salvador, João Xavier de Araújo-Júnior & , Emanuel Tenório Paulino, Jessyka Carolina Galvão da Silva, Êurica Adélia Nogueira Ribeiro, Isac Almeida de Medeiros (Journal of Applied Pharmaceutical Science, 2017)
Aspidosperma species have been traditionally used for the treatment of cardiovascular disease. These species are important sources of indole alkaloids, which are responsible for different cardiovascular effects. Based on this premise, and as there are still no studies related to the cardiovascular effects of the ethanolic extract from the stem bark of Aspidosperma tomentosum (EEAT). The goal of the survey was to characterize the mechanism of the vasorelaxant action of EEAT in isolated rat mesenteric rings and to establish its antihypertensive activity. The mean arterial pressure (MAP) and Heart Rate (HR) were measured in hypertensive rats through a catheter implanted in abdominal aorta via the femoral artery. The vasodilator effect of EEAT in isolated pre-contracted rat mesenteric rings was examined. The bioactive extract was investigated via mass spectrometry fingerprinting. EEAT induced relaxation in mesenteric rings pre-contracted with Phe independent of the endothelium. In denuded rings, when incubation with KCl 20 mM or TEA did not change the relaxation. EEAT inhibited the concentration-response curves induced by CaCl2 or Phe and inhibited 80 mM KCl-induced contraction. In pre-contracted preparations with BayK 8644, the EEAT induced relaxation. The transient contraction induced by Phe was inhibited. The oral administration of EEAT reduced MAP and did not alter the HR. Phenolic acids, flavonoids, and indole alkaloids were identified in EEAT. In conclusion, the EEAT induced vasorelaxation through a blockade of Ca2+ channels and inhibition of the mobilization of Ca2+ of the IP3-sensitive Ca2+ stores and caused an antihypertensive effect.
Keywords: Aspidosperma tomentosum, vasorelaxant activity, mesenteric rings, Ca2+ influx, antihypertensive effect, rats.